2016
DOI: 10.1038/srep31081
|View full text |Cite
|
Sign up to set email alerts
|

Changing trend of HIV, Syphilis and Hepatitis C among Men Who Have Sex with Men in China

Abstract: Dearth of information regarding the trend and correlates of HIV, syphilis and Hepatitis C (HCV) in a country-wide sample of understudied though high-risk Chinese men who have sex with men (MSM) called for a comprehensive serial cross-sectional study. Using a multistage mixed-method strategy, 171,311 MSM from 107 selected cities/counties in 30 provinces of mainland China, were interviewed and tested. Descriptive, bivariate, multivariate and Cochran-Armitage trend analyses were conducted using SAS 9.2. During 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 38 publications
(63 reference statements)
3
52
1
2
Order By: Relevance
“…The HIV epidemic is severe among gay, bisexual and other men who have sex with men (GBMSM) in China, as the overall HIV prevalence and incidence in this group are both high and increasing (9.9% and 5.6 per 100 person-year in 2016) [1,2]. In Hong Kong, China, where the study was conducted, the HIV prevalence and incidence among GBMSM was 6.54% and 1.0 per 100 person-year in 2017, respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The HIV epidemic is severe among gay, bisexual and other men who have sex with men (GBMSM) in China, as the overall HIV prevalence and incidence in this group are both high and increasing (9.9% and 5.6 per 100 person-year in 2016) [1,2]. In Hong Kong, China, where the study was conducted, the HIV prevalence and incidence among GBMSM was 6.54% and 1.0 per 100 person-year in 2017, respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the Asia‐Pacific, sexual transmission of HCV has not been commonly reported. Recent studies in different cities in China have not shown increased or increasing HCV incidences among MSM . Needle‐sharing among injection drug users (IDUs) rather than male‐to‐male sex remains the most common cause of HCV spread in China and Vietnam .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented that migrants have high risky sexual behaviors and STIs than non-migrants [4][5]. Male Migrants seek sexual relationships in the area of the workplace; become part of a newer sexual network, which may in part explain the rise in STI incidence[6].…”
Section: Introductionmentioning
confidence: 99%